2017
DOI: 10.5010/jpb.2017.44.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Three transcripts of EDS1-like genes respond differently to Vitis flexuosa infection

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract Enhanced disease susceptibility1 (EDS1) is a regulator of basal defense responses required for resistance mediated by TIR-NBS-LRR containing R proteins. We identified three transcripts of EDS1-like gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In contrast, SA signaling is typically involved in plant resistance to biotrophic pathogens [53], with the positive SA regulator EDS1 conferring basal defense against various pathogens by interacting with a subset of plant resistance (R) genes [54]. Three EDS1-like genes with distinct expression patterns were identified in V. flexuosa inoculated with E. ampelina, and two of them(VfEDL2 and VfEDL3)are known to be induced by infection [55]. In our study, up-regulation of EDS1 at the early time point in the HR grape is indicative of an SA pathway response in the resistant grape.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SA signaling is typically involved in plant resistance to biotrophic pathogens [53], with the positive SA regulator EDS1 conferring basal defense against various pathogens by interacting with a subset of plant resistance (R) genes [54]. Three EDS1-like genes with distinct expression patterns were identified in V. flexuosa inoculated with E. ampelina, and two of them(VfEDL2 and VfEDL3)are known to be induced by infection [55]. In our study, up-regulation of EDS1 at the early time point in the HR grape is indicative of an SA pathway response in the resistant grape.…”
Section: Discussionmentioning
confidence: 99%
“…Jayasankar et al (2003) have reported that the spore germination and the hyphal growth of E. ampelina are significantly inhibited by a V. vinifera thaumatin-like protein. Several genes encoding β-1,3glucanase , nucleotide-binding site domain proteins (Islam et al, 2015a;Seehalak et al, 2011), receptor-like protein kinase (Islam et al, 2015b), glutathione S-transferase (Ahn et al, 2016), Mlo-like proteins (Islam & Yun, 2016a), carboxylesterase proteins (Islam & Yun, 2016b), and EDS1-like proteins (Islam & Yun, 2017) are responsive genes to E. ampelina infection, indicating that these genes may participate in the disease-resistance response.…”
Section: G Ene Ti C S and Hos T Re S Is Tan Cementioning
confidence: 99%
“…Ahn et al (2014a) de novo assembled the transcriptome of the resistant Korean species V. flexuosa inoculated with the pathogen. This analysis led to the identification and subsequent characterization of many resistance related responsive genes to E. ampelina inoculation, such as β-1,3-glucanase genes (Ahn et al, 2014b), RPS5-like genes (Islam et al, 2015a), receptor-like protein kinase (RLK) genes (Islam et al, 2015b), Mlo-like genes (Islam and Yun, 2016a), carboxylesterase genes (Islam and Yun, 2016b), glutathione S-transferase genes (Ahn et al, 2016) and EDS1-like genes (Islam and Yun, 2017). Several V. vinifera thaumatin-like proteins ( VvTLP ) genes responsive to anthracnose were also recently identified (Yan et al, 2017).…”
Section: Grapevine-ascomycete Interactionmentioning
confidence: 99%